Feasibility of pre-scrotal castration approach in boars: 30 cases - Antônio Carlos L. Câmara; Kaique Nogueira; João Vagner S. Junqueira; Tiago S. Andrade; Antonio Raphael Teixeira-Neto; Rita de Cássia Campebell (Pesquisa Veterinária Brasileira, 2023)
ABSTRACT: Since the first reports of boar castration, the anesthesia, surgery, and especially the restraint for surgical wound management of large and strong boars may be challenging. Most frequent complications include hemorrhage, excessive edema, infection, abscess, scirrhous cord, inguinal hernia, seroma, hematoma, and death. In order to diminish those complications, we hypothesized that the pre-scrotal approach would be a successful method for orchiectomy in boars and that the complication rate would be low, facilitating post-surgical handling on the commercial swine breeding farms by the owners or handlers. Therefore, the present study aimed to describe our experience performing castration in boars using a pre-scrotal approach on farm-setting. Thirty commercial-breed male boars (weighing 255-410kg) were submitted to dissociative anesthesia protocol and local anesthesia. An 8-10cm skin incision was made cranially to the hemiscrotum, and subcutaneous tissue was bluntly dissected, reaching the tunica dartos, fascia, and vaginal tunica. Mesorchium was bluntly dissected to separate, and a double size-0 transfixion ligature was placed around the spermatic cord that was sharply transected. The procedure was repeated on the contralateral testis using the same skin incision. Short-term complication was restricted to mild scrotal edema in 12 (40%) boars. No wound exudate, surgical site infection or death related to the surgery was recorded. On the long-term follow-up (≥4 months’ post-surgery), all owners stated that the boar was subsequently used as intended (slaughter after the proper boar taint withdrawal time) and their satisfaction with the low degree of difficulty in handling the post-operative care. Herein, the overall complication rate was considered low, the mortality rate was zero, and the pre-scrotal castration approach was successfully performed in all boars. These features confirm the technique as a safe procedure for orchiectomy in boars. Additionally, abolishing the daily dressing of surgical wounds required in open castration techniques, especially when surgical site infection occurs, may provide better welfare for the boars.